Genetic variation in MAOA modulates prefrontal cortical regulation of approach-avoidance reactions - Ernst, Lena; Lutz, Elisabeth; Ehlis, Ann-Christine; Fallgatter, Andreas J.; Reif, Andreas; Plichta, Michael M. (Neuropsychobiology, 2013)
Background: Regulation of automatic approach and avoidance behavior requires affective and cognitive control, which are both influenced by a genetic variation in the gene encoding Monoamine Oxidase A (termed MAOA-uVNTR). Methods: The current study investigated MAOA genotype as a moderator of prefrontal cortical activation measured with functional near-infrared spectroscopy (fNIRS) in 37 healthy young adults during performance of the approach-avoidance task with positive and negative pictures. Results: Carriers of the low- compared to the high-expressing genetic variant (MAOA-L vs. MAOA-H) showed increasing regulatory activity in the right dorsolateral prefrontal cortex (DLPFC) during incompatible conditions (approach negative, avoid positive). This might have been a compensatory mechanism for stronger emotional reactions as shown in previous studies and might have prevented any influence of incompatibility on behavior. In contrast, fewer errors but also lower activity in the right DLPFC during processing of negative compared to positive stimuli indicated MAOA-H carriers to have used other regulatory areas. This resulted in slower reaction times in incompatible conditions, but - in line with the known better cognitive regulation efficiency - allowed them to perform incompatible reactions without activating the DLPFC as the highest control instance. Carriers of one low- and one high-expressing allele lay as an intermediate group between the reactions of the low- and high-expressing groups. Conclusions: The relatively small sample size and restriction to fNIRS for assessment of cortical activity limit our findings. Nevertheless, these first results suggest monoam-inergic mechanisms to contribute to interindividual differences in the two basic behavioral principles of approach and avoidance and their neuronal correlates.
Gesehen am 24.03.2022